Turismo rural e desenvolvimento local: estudo da rota gastronômica de Santa Maria - Silveira Martins, RS - Lindner, Michele (2007)
In Brazil, the non-agricultural rural activities have been growing more and more. This change has originated from the continuous decline of the capacity of agriculture in maintaining as well as generating working vacancies and income. This study analyses rural tourism as a way to generate job opportunities and also income, by studying the direct commercialization as a tool for promoting and valuing the local food products in the Touristic and Gastronomic Route Santa Maria Silveira Martins, starting with the identification of producers inserted in the Route, the kinds and origins of the commercialized foods, the motivations for the commercialization of the products, the profile of the consumers (tourists) and their reasons for consuming the products. Thus, the investigation has sought to discover to what extent the touristic activity has been contributing for the local development, through the direct commercialization of the food products (transformed and In natura ). The study has been based in qualitative and quantitative/descriptive methods, being that the data collection has been carried out through interviews and questionnaires with informers responsible for the touristic places of interest and questionnaires applied to the consumers/tourists present in these places during the field research, besides the data obtained through a consult in folders, reports and other documents. The obtained results reveal that the touristic activity and the commercialization of the products in the Route have brought about great benefits not only for part of the population directly involved with the activity, but also for a part indirectly involved, since the great majority of the commercialized products com from this region. Nevertheless, in terms of local development, the activity still demonstrates being insufficient for its promotion. It is considered that the development of tourism in this locality requires a greater specialization, which means the necessity of a broad planning of the activity, investments in infra-structure and in human resources, in the quality of the commercialized products and in other aspects such as a bigger involvement of the local population where the activity is developed.